FRANCHISE CONCEPT AS POSSIBLE MARKETING STRATEGY FOR TOURISM DEVELOPMENT - Svetlana Mihić; Branka Maksimović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
For a long period in the world, especially at the field of tourist services distribution, franchising system was been applied very successfully and example for this are world famous hotel chains. A modern man has found him self in a swirl of everyday changes and entered unprepared in to one entirely new world of assumption, which was unattended and ignored at this area for many years. Lack of necessary multidiscipline knowledge, visionary and entirely new manner of things placing lead to the situation that present man wonders seeking him in a world of business, but mistakes are often incorrigible. Because of that there is no real reason why this well sampled system, system of franchising, have been implemented in our frames as well, only when distribution is in matter, before all in vital tourist services. In the modern business conditions, most studies show irrefutable fact that more than 90% of independent business fail even in the first three years of work. Though, franchising system imposes itself as a model of distribution organization, as concerning products so as concerning services, which provides a certain independence in business dealings, as well as possibility to act in the frame of big and good developed systems.